Essential histidine residues in Bombyx mori nucleopolyhedrovirus GP64 mediate pH-dependent membrane fusion - Haijue Tian; Kai Chen; Xinyu Li; Ying Xu; Bifang Hao; Jinshan Huang (Microbiology Spectrum)
ABSTRACT Enveloped viruses initiate host cell entry through membrane fusion mediated by viral fusion proteins. In group I alphabaculoviruses, the class III membrane fusion protein GP64 mediates virus–cell fusion under acidic conditions. In Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV), three key histidine residues in GP64 function as pH sensors. In contrast, Bombyx mori nucleopolyhedrovirus (BmNPV)—despite its high genomic similarity to AcMNPV—exhibits a lower fusion pH threshold and retains its signal peptide in host cells, introducing additional histidine residues absent in AcMNPV GP64. To elucidate the role of these histidines, we generated 14 single-histidine-to-alanine mutants of BmNPV GP64 and evaluated their expression, membrane localization, and fusogenicity in BmN cells. Although all mutants correctly formed trimers and localized to the cell surface, several mutations either abolished or diminished low-pH-induced syncytia formation and altered the binding profile of the conformation-sensitive AcV1 antibody. Moreover, the reintroduction of these mutants into a gp64-null bacmid revealed that specific residues (H168, H172, H342, and H351) are essential for pH-induced conformational transitions and viral infectivity, thereby underscoring their role as pH sensors. These results not only enhance our understanding of the molecular basis underlying BmNPV GP64-mediated membrane fusion but also lay the foundation for developing targeted strategies to control BmNPV infections in economically important silkworms.IMPORTANCEUnderstanding the molecular determinants of viral fusion is essential for elucidating virus-host interactions and adaptation. This study provides novel insights into how specific histidine residues in BmNPV GP64 govern pH-dependent conformational changes necessary for membrane fusion. By dissecting the contributions of these residues through mutagenesis and functional assays, our work clarifies differences in fusion activation between closely related alphabaculoviruses. Such insights are crucial not only for advancing our basic knowledge of viral entry mechanisms but also for informing the design of antiviral strategies that could interfere with viral fusion processes. The identification of critical pH-sensing residues in BmNPV GP64 lays a foundation for future structural studies and understanding pH-dependent activation in other enveloped viruses.